Pathology Of Vascular-Platelet And Coagulation Hemostasis In Coronavirus Infection (Literature Review) (Eurasian Medical Research Periodical, 2022)
The literature review provides the relevance of coronavirus infection, describes in detail the mechanisms of development of endothelial dysfunction, cytokine storm, imbalance in the coagulation system and the development of disseminated intravascular coagulation syndrome in coronavirus infection. It has been analyzed the widely used hemostasiological indicators in general practice, which are important in determining the prognosis of patients with coronavirus infection: platelets, prothrombin time, active partial thromboplastin time, D-dimer and fibrinogen